Trends in Brazilian and global television journalism - Wainberg, Jacques A. (2012)
This study deals with TV news trends in Brazil and worldwide as well as the reception of this content by Brazilians. The data were collected by content analysis of Jornal Nacional and Jornal da Cultura and 34 TV news programs of 17 countries. A survey was applied in all regions of Brazil as well. Finally, it deals with some news selection criterions used in the selection of these international news